Variables epidemiológicas y severidad del cáncer de mama en mujeres atendidas en el Hospital Regional de Loreto Iquitos 2019 - Heredia Gonzales, Patricia Juliana (2024)
The objective of this research was to determine the association between epidemiological variables and severity of breast cancer in women treated at Hospital Regional de Loreto Iquitos 2019. The type of research was quantitative, the design was non-experimental, descriptive, correlational and retrospective. The sample was made up of 83 medical records of women diagnosed with breast cancer. The technique used was documentary review and the instruments were the Epidemiological Data Sheet for Women with Breast Cancer and the Data Sheet for Classifying the Degree of Severity of Breast Cancer. For data processing, the SPSS version 24.0 statistical package was used; for the bivariate analysis, the chi-square statistical test (x2) was used with a 95% significance level with alpha α = 0.05. The results were: 67.5% were between 36 and 60 years old, 72.3% were housewives, 48.2% were cohabitants, 55.6% had been ill for 4 to 7 years, 81.9% came from urban areas. Regarding the degree of severity of breast cancer, 32.5% presented Grade III. Conclusion, it was demonstrated that there is an association between the degree of severity of breast cancer: age (p = 0.001), level of education (p = 0.000), duration of illness (p = 0.038), and origin (p = 0.011). Likewise, no association was found with: occupation (p= 0.419) and marital status (p = 0.786).